Determination of structural behavior of precast foamed concrete sandwich panel - Amran, Mugahed Yahya Hussein (2016)
Precast Foamed Concrete Sandwich Panel (PFCSP) has the ability to act as a wall bearing and flooring element that complies with the requirements of structural efficiency and thermal insulation of building components. It has the potential for use as an industrialised building system component for low-rise residential buildings.The development of housing remains a major worldwide challenge for construction industries in many countries due to financial constraints and lack of appropriate technologies. The problem is further compounded by rapid increase of population.Also, the existing precast concrete sandwich panels act in a semi-composite behavior due to several factors related to shear connectors used. Therefore, a study to improve on the structural composite performance is extremely required, as most of the current precast concrete structures are deemed as heavy systems. Hence, the reduction on the self-weight of PCSP becomes highly imperative, particularly for use at construction sites with low load-bearing capacity grounds.This study has the objectives to determine the parameters related to structural behavior of PFCSP served as load-bearing wall and floor systems. The study also determines the properties of foamed concrete for use in the production of PFCSP. In order to evaluate the performance of the developed PFCSP elements, PFCSPs were subjected to loads in various directions, including axial, in-plane and out-of-plane loads. An analytical study and experimental tests were conducted to evaluate the structural performance of the PFCSPs subjected to loads in various directions. An experimental study comprising thirty (30) PFCSPs and three (3) PCSPs with one panel was set as control, as each test was conducted under three different full-scale loadings (12 PFCSPs under axial load, 6 PFCSPs under in-plane shear load, and 12 PFCSPs under out-of-plane load). Foamed concrete with 24.83 MPa and 25.73 MPa was obtained as the potentially viable grades to produce the structural concrete wythes of the PFCSPs as load-bearing wall and slab elements, respectively. Foamed concrete wythes act as structural rigid elements. Important parameters, such as slenderness (H/t) and aspect ratios (L/d) were investigated using different variables.The composite action under different imposed load conditions was studied and revealed a high structural composite performance. Further, a FEA parametric study was carried out to study similar parameters conducted via experimental tests to study the performance. Also, the theoretical investigations are conducted using design codes and theoretical expressions of previous researchers. Comparisons are made between the results obtained from experimental tests and non-linear FEA models studies for the purpose of validation. Analysis of results found that the ultimate bearing strength was decreased by approximately 26.3% and 111% for an increase of H/t from 14 to 24 and 13.33 to 28.57, respectively, as obtained from experimental works. However, using the 2-D FEA simulation models, the bearing capacity was decreased by almost 9.9% and 89%. Under in-plane shear load, the reduction in ultimate in-plane strength was approximately 36.14% and 28.07% for an increase of H/t from 14 to 24, as obtained from tests and the 2-D FEA models, respectively. The ultimate bearing capacity of the developed PFCSP walls was obtained to be at least 9 times larger than the required, to resist typical two-storey ultimate design loads. Furthermore, it has been found that the ultimate flexural strength capacity was decreased by around 50% and 52.3% with an L/d increase from 18.33 to 26.67 and from 16.18 to 23.53 of the two identical PFCSP groups with the depths of 150 and 170 mm, respectively, as obtained experimentally. Verification of the result using the 2-D FEA simulation models indicated a reduction in ultimate strength capacity of about 69.6% and 79.2%, Respectively.Therefore, it is concluded that the developed PFCSP is suitable as a load bearing element, and can be applicable and safe for a wall system for two-storey buildings,and PFCSP has a practical use as floor slabs. The summary and conclusions of the major findings of this study together with the recommendations for further work arepresented in Chapter VII.